Gamelan Data Repository: The Implementation of Information and Communication Technology Preserving the Balinese Traditional Musical Orchestra - Gede Rasben Dantes (Universitas Pendidikan Ganesha, 2022)
As the knowledge to build Balinese orchestra are passed down from generation to another within the clan, the orchestras across makers and across areas in Bali show subtle but distinctive differences in their tones, which may be altered when the knowledge is passed down manually. Research aimed at digitalizing these distinct differences in the creations of the Balinese Orchestra across craftsmen clans in Bali is conducted as an effort for preserving the unique differences produced by the respective clans through the development of a system prototype and database for storing the tones in the orchestra sets. The steps design to attain these purposes comprised of (1) analyzing the needs of preserving the Balinese Orchestra and mapping the problems faced by traditional craftsmen in maintaining standard tones; (2) designing a system to record the standard tones among craftsmen in Bali, i.e. sampling two most two groups of craftsmen from two regencies recognized as having the most distinctive tones in Bali, namely South of Bali and North of Bali; (3) developing the prototype; and (4) developing the database of Balinese Orchestra. When the database is ready, it will provide a reference for craftsmen to standardize their sets according to the intended tradition while opening a wide possibility of uses ranging from evaluation to the creation of collaborative musical compositions across media, while at the same time preserving the standardized tone in digitalized storage.